Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/pi.2408
|View full text |Cite
|
Sign up to set email alerts
|

A novel polymer composite with double positive‐temperature‐coefficient transitions: effect of filler–matrix interface on the resistivity–temperature behavior

Abstract: BACKGROUND: Sn–Pb alloy‐filled high‐density polyethylene (HDPE) composites exhibit double positive‐temperature‐coefficient (PTC) behavior, with the first transition at the melting point of HDPE and the second at that of Sn–Pb alloy. The objective of this study is to improve the reversibility and reproducibility of double‐PTC transitions of these composite materials by enhancing the filler–matrix interface. RESULTS: Fourier transform infrared spectroscopy, surface wettability and dynamic mechanical and rheologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The temperature-resistivity characteristics of carbon black particles filled polymer composites were widely investigated [35]. It was found that in the vicinity of glass transition temperature of the polymer, some conductive particles filled polymer composites could exhibit a positive temperature coefficient in resistivity (PTCR) effect [36].…”
Section: Effect Of Temperature On the Electrical Propertiesmentioning
confidence: 99%
“…The temperature-resistivity characteristics of carbon black particles filled polymer composites were widely investigated [35]. It was found that in the vicinity of glass transition temperature of the polymer, some conductive particles filled polymer composites could exhibit a positive temperature coefficient in resistivity (PTCR) effect [36].…”
Section: Effect Of Temperature On the Electrical Propertiesmentioning
confidence: 99%
“…Carbon nanotubes (CNTs) have been considered as one of the best conductive fillers for CPCs due to their large aspect ratio and ultrahigh conductivity , . Recently, CPCs have been investigated extensively to act as sensors for various stimuli, such as strain, temperature and vapor . In terms of strain sensing, a wide range of applications have been proposed, including smart textiles,, health monitoring, wearable electronics, movement sensors, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Yi et al [23–25] reported the use of Sn‐Pb alloy as conducting filler in polystyrene (PS) matrix that showed PTC transition of PS/Sn‐Pb composites near the melting point of the filler ( T m : 183°C) instead of the matrix polymer (PS). Zhang et al [26–28] observed double PTCR effect in low melting alloy‐filled semicrystalline polymer composites (HDPE/Sn‐Pb). However, limited reversibility and reproducibility of the double‐PTCR behavior restricted the applications of these composites.…”
Section: Introductionmentioning
confidence: 99%